Hubungan Antara Pengetahuan, Sikap dan Perilaku Ibu yang Mempunyai Anak Usia 12-36 Bulan dengan Pemberian Imunisasi Dasar Lengkap di Posyandu Mas Sirnagalih Tamansari Kabupaten Bogor - Putri Azahra Hifniwati; Aditiawarman; Zainal Abidin; Astrid Sulistomo; Wawang Sukarya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Immunization is the act of providing protection or immunity to a child's body by injecting a vaccine or serum from a disease that has been weakened into the body. According to Riskesdas data in 2018, the coverage of fully immunized children was 57.9%, incomplete 32.9% and did not get immunized 9.2%. This study aims to determine the relationship between knowledge, attitudes and behavior of mothers with the provision of basic immunization in infants at Posyandu Mas Sirnagalih Tamansari, Bogor Regency. This research method is observational analytic with cross sectional approach. Data were collected using a special questionnaire to determine the knowledge, attitude and behavior of mothers. Data were analyzed by Fisher statistical test using Statistical Package for the Social Sciences (SPSS version 27) program. The results showed that the distribution of subjects based on incomplete immunization coverage was 37.00%. The distribution of subjects based on poor knowledge of immunization was 8.70%; negative attitude towards immunization 4.30% and poor behavior towards immunization 17.40%. There is a significant relationship between negative attitudes and bad behavior of mothers with incomplete basic immunization (CI 90%; p < 0.1).